Perceived Convenience, Perceived Benefits, Perceived Price, Trust, Attitude and Decision to Use of The Shopee Marketplace - Setyaningrum, Angela Selvia; Septyanto, Dihin; Mariam, Siti (Majalah Ilmiah Bijak, 2023)
The main objective of this study is to analyze the effect of perceived convenience, perceived benefits, perceived price and trust on usage decisions through attitudes towards shopee users. The sampling technique used in this study was purposive sampling with the nonprobability sampling method. The number of respondents used in this study amounted to 105 respondents with the criteria of First University Students and having transacted at least five times using Shopee. The analytical method used is Partial Least Square Structural Equation Modeling (PLS-SEM). The results can be concluded that perceived convenience, perceived benefits, perceived price and trust felt by users can improve attitudes so as to attract consumers aged over 17 years and over to have a decision to use Shopee. In this case, perceived benefits and perceived price have not been able to increase the decision to use Shopee.